PRINSIP-PRINSIP KEADILAN DALAM PENETAPAN HARGA PERSPEKTIF ISLAM - Abd. Rahman; Nahei nahei (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
Price determination is a crucial aspect of economic activity that affects the balance between producers and consumers. In Islam, the principle of justice serves as a fundamental foundation that must be applied in every economic transaction to ensure fairness for all parties involved. This study aims to analyze the principles of justice in price determination from an Islamic perspective and its relevance to modern economic challenges. A qualitative approach with a literature review method was employed, analyzing Qur'anic verses, Hadiths, and Islamic economic literature. The findings reveal that Islamic principles of justice emphasize transparency, honesty, and the avoidance of harmful practices such as hoarding and price manipulation. Moreover, the study highlights that applying the principle of justice in price determination not only maintains the balance between producers’ and consumers’ rights but also promotes market stability and social harmony. This research contributes significantly to the understanding of the relevance of Islamic values of justice to contemporary economic practices and provides practical guidance for economic actors and policymakers in creating a more equitable and sustainable market system.